Contrasting patterns of selection between MHC I and II across populations of Humboldt and Magellanic penguins - Sallaberry Pincheira, Nicole (2016)
The evolutionary and adaptive potential of populations or species facing an emerginginfectious disease depends on their genetic diversity in genes, such as the major histocompatibilitycomplex (MHC). In birds, MHC class I deals predominantly with intracellularinfections (e.g., viruses) and MHC class II with extracellular infections (e.g.,bacteria). Therefore, patterns of MHC I and II diversity may differ between species andacross populations of species depending on the relative effect of local and global environmentalselective pressures, genetic drift, and gene flow. We hypothesize thathigh gene flow among populations of Humboldt and Magellanic penguins limits localadaptation in MHC I and MHC II, and signatures of selection differ between markers,locations, and species. We evaluated the MHC I and II diversity using 454 next-generationsequencing of 100 Humboldt and 75 Magellanic penguins from seven differentbreeding colonies. Higher genetic diversity was observed in MHC I than MHCII for both species, explained by more than one MHC I loci identified. Large populationsizes, high gene flow, and/or similar selection pressures maintain diversity but limitlocal adaptation in MHC I. A pattern of isolation by distance was observed for MHC IIfor Humboldt penguin suggesting local adaptation, mainly on the northernmost studiedlocality. Furthermore, trans-speciesalleles were found due to a recent speciationfor the genus or convergent evolution. High MHC I and MHC II gene diversity describedis extremely advantageous for the long-termsurvival of the species.